A Case Series Exploring Hyperhomocysteinemia as a Prothrombotic Risk Factor (GAIMS Journal of Medical Sciences, 2024)
The role of hyperhomocysteinemia (Hhcy) as a prothrombotic risk factor has been researched and debated over many decades. Several prospective and retrospective studies have established the association of Hhcy as a modifiable risk factor in both arterial and venous thrombosis. This case series of nine patients with either recurrent or unprovoked thrombosis and thrombosis occurring at unusual sites aims to elucidate the association between Hhcy and thrombotic events as an independent risk factor. This study underscores the importance of screening for homocysteine (Hcy) levels for early management of high-risk patients and contributes to the existing evidence of the thrombogenic effects of Hcy, thereby highlighting future research to improve management guidelines and preventive protocols.